2021
DOI: 10.1186/s12904-021-00840-0
|View full text |Cite
|
Sign up to set email alerts
|

Community palliative care services on addressing physical and psychosocial needs in people with advanced illness: a prospective cohort study

Abstract: Background The integration of palliative care into primary health care has been advocated to improve its accessibility and the continuity of care. Recent studies on such an approach have mainly focused on health care cost and utilization. This study aims to evaluate the effects of a community interdisciplinary palliative care program on the symptom experience of patients with advanced disease. Methods A prospective cohort study was conducted. The I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…In accord to findings from patients with end‐stage renal failure (Ng et al, 2020), adults at EOL actively withdrew from social networks because of embarrassing symptoms, inability to contribute to group activities, unable to cope with relative's worries, and unable to be understood by family. This further led to their dysfunctional communication (e.g., avoidance from family members or friends) (Chan et al, 2021). Therefore, it is crucial to re‐engage adults at EOL into social activities, and more importantly, meaningful relationships with their significant ones.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In accord to findings from patients with end‐stage renal failure (Ng et al, 2020), adults at EOL actively withdrew from social networks because of embarrassing symptoms, inability to contribute to group activities, unable to cope with relative's worries, and unable to be understood by family. This further led to their dysfunctional communication (e.g., avoidance from family members or friends) (Chan et al, 2021). Therefore, it is crucial to re‐engage adults at EOL into social activities, and more importantly, meaningful relationships with their significant ones.…”
Section: Discussionmentioning
confidence: 99%
“…This further led to their dysfunctional communication (e.g., avoidance from family members or friends) (Chan et al, 2021). Therefore, it is crucial to re-engage adults at EOL into social activities, and more importantly, meaningful relationships with their significant ones.…”
Section: Discussionmentioning
confidence: 99%
“…This 2) is in line with a recent local research that showed that comprehensive care was considered an important component of community end-of-life care and contributed to positive outcomes. 15 The multidimensional nature of these services was also aligned with the core philosophy of PEoLC via the provision of holistic care. 2 Furthermore, the current findings also reflected the development of a community PEoLC model that featured social-medical collaboration, which extended beyond traditional social care services to promote holistic care through a partnership with the healthcare sector.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 Only a few studies have attempted to explore the components, outcomes, and mechanisms of community PEoLC services in Hong Kong. [15][16][17] Several key findings have been reported: the components of community PEoLC services are instrumental and comprehensive in nature, and some positive benefits include improved emotional and social well-being and enhanced quality of life. However, rather than examining the PEoLC services in the context of a broad range of service programs and settings, the available studies exclusively targeted terminally ill patients from a particular care program, thereby limiting the understanding of the current status of existing community PEoLC services in Hong Kong.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies in HK usually focused on single disease groups such as cancer or other neurological conditions, employing small samples (less than 70 participants). 12,23 Their findings, however, indicate that comprehensive, holistic EoLC intervention that enables terminally ill patients to receive care at home, is logical and attractive care model in HK. 12,23 This study sought to provide preliminary evidence of the effectiveness of a psychosocially emphasized home-based EoLC intervention for terminally ill patients in HK, employing the 17-item IPOS measure.…”
Section: Introductionmentioning
confidence: 99%